2020
DOI: 10.1021/jacs.0c08589
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Optical Properties of BODIPY Dyes by Noncovalent Dimerization within a Flexible Coordination Cage

Abstract: Aggregation of organic molecules can drastically affect their physicochemical properties. For instance, the optical properties of BODIPY dyes are inherently related to the degree of aggregation and the mutual orientation of BODIPY units within these aggregates. Whereas the noncovalent aggregation of various BODIPY dyes has been studied in diverse media, the ill-defined nature of these aggregates has made it difficult to elucidate the structure–property relationships. Here, we studied the encapsulation of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 76 publications
7
45
0
Order By: Relevance
“…The result is in good agreement with the experimental data (Figure 5 c), on the basis of the number of the absorption bands and their relative intensity. On the other hand, the calculated H‐ and J‐type dimers (Figure 5 e, center and right), which have been reported by the Klajn group, [19c] as well as other calculated dimers (except for L‐shaped dimers) have only a single, prominent absorption band in the range of 400 to 600 nm (Figure S38) [11] . The calculated energy of the L‐shaped dimer is higher and lower than those of the H‐ and J‐type dimers, respectively (Figure 5 e).…”
Section: Figuresupporting
confidence: 52%
“…The result is in good agreement with the experimental data (Figure 5 c), on the basis of the number of the absorption bands and their relative intensity. On the other hand, the calculated H‐ and J‐type dimers (Figure 5 e, center and right), which have been reported by the Klajn group, [19c] as well as other calculated dimers (except for L‐shaped dimers) have only a single, prominent absorption band in the range of 400 to 600 nm (Figure S38) [11] . The calculated energy of the L‐shaped dimer is higher and lower than those of the H‐ and J‐type dimers, respectively (Figure 5 e).…”
Section: Figuresupporting
confidence: 52%
“…Rather unexplored aspects that may influence the triplet excited state population are: (i) the effect of aggregation in solid state or confined environments compared to solution studies, 108 reminiscent of the co-facial π-stacked arrangements of chromophores found in nature ( e.g. , photosynthetic reaction center); (ii) the radical pair induced ISC that is expected to have potential applications in the field of solar energy conversion; (iii) the switching behavior of BODIPY dyads and dimers by external stimuli that can modify the energy of the charge transfer state; (iv) the shift of BODIPY absorption to the red and near-infrared spectral region coupled to efficient triplet population with potential applications in biomedicine.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…101 When BODIPY dyes are involved in electron transfer processes, the chemical stability of the so-formed radical cation or anion is a key requisite: the presence of alkyl substituents in the positions 2,3,5 and 6 improves their chemical stability, preventing dimerization/ polymerization processes. 5 Rather unexplored aspects that may inuence the triplet excited state population are: (i) the effect of aggregation in solid state or conned environments compared to solution studies, 108 reminiscent of the co-facial p-stacked arrangements of chromophores found in nature (e.g., photosynthetic reaction center); (ii) the radical pair induced ISC that is expected to have potential applications in the eld of solar energy conversion; (iii) the switching behavior of BODIPY dyads and dimers by external stimuli that can modify the energy of the charge transfer state; (iv) the shi of BODIPY absorption to the red and near-infrared spectral region coupled to efficient triplet population with potential applications in biomedicine. 100 In conclusion, the present challenge in the development of light energy conversion and photocatalysis is to design organic dyes which couple (i) strong visible absorption, (ii) efficient population of a long-lived triplet excited state T 1 and (iii) strong reducing and/or oxidizing power.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, the polycationic cages due to the limited space inside the cavity force even the J-preferring BODIPY dyes to form the Haggregates. This phenomenon opens the new possibilities of reversible molecular switching between the different type of arrangements of BODIPY dyes, leading to the controlled tunability of their absorption and emission [16]. The significance of these findings together with the general lack of control upon modification of the aggregation mode invokes the strong necessity of the thorough knowledge of the nature of intermolecular interaction in BODIPY dimers and-further on-higher aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…BODIPY dimer formation remains of interest nowadays when the new covalent or non-covalent ways of controlling the intramolecular arrangements in BODIPY aggregates is desired for instance for detection of analytes in aqueous biological environments [8,16]. The explanation of the modulation of the photophysical properties of BODIPY can be provided on the basis of the exciton model proposed by Kasha [8,17,18].…”
Section: Introductionmentioning
confidence: 99%